Uridine, Thymidine and Inosine Used as Chiral Stationary Phases in HPLC - Zhang, Mei; Zi, Min; Wang, Bang-Jin; Yuan, Li-Ming (Asian Journal of Chemistry, 2014)
In this paper, we present the first enantioseparations research using thymidine, uridine and inosine as chiral stationary phase bonded to silica gel via 3-(triethoxysilyl)propyl isocyanate in HPLC. Thymidine and uridine chiral stationary phases possess enantioseparation selectivity for alcohols, amines, ketones and carboxylic acids to some degree in normal-phase and reversed-phase mode. This work indicates that nucleoside or deoxynucleoside can be useful for the separation of enantiomers in the liquid phase as a new kind of chiral stationary phase.